2019
DOI: 10.1016/j.jor.2019.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant platelet derived growth factor-BB and hyaluronic acid effect in rat osteoarthritis models

Abstract: Osteoarthritis (OA) arises from imbalance of cartilage metabolism between the synthesis and degradation of type II collagen by the chondrocyte. Collagen type II degradation is characterized by increase in the biomarker of Ctelopeptide fragment of type II collagen (CTX-II), while the anabolic process of cartilage is characterized by an increase in the biosynthesis of procollagen amino terminal N-propeptide type IIA (PIIANP). Platelet derived growth factor (PDGF) with Hyaluronic Acid (HA) as a potent growth fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Therefore, preventing or curing OA by intervening in chondrocyte apoptosis would be a valid strategy to modulate cartilage degeneration. Wang et al and Ding et al found that inhibiting apoptosis could be a potential therapeutic strategy for OA treatment A previous report showed that intra‐articular injection of 10 ng/mL recombinant PDGF‐BB combined with hyaluronic acid could alleviate OA by promoting the anabolism of collagen II and inhibiting catabolism in rats 16 . Based on the above description, PDGF‐BB promotes proliferation 12 .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Therefore, preventing or curing OA by intervening in chondrocyte apoptosis would be a valid strategy to modulate cartilage degeneration. Wang et al and Ding et al found that inhibiting apoptosis could be a potential therapeutic strategy for OA treatment A previous report showed that intra‐articular injection of 10 ng/mL recombinant PDGF‐BB combined with hyaluronic acid could alleviate OA by promoting the anabolism of collagen II and inhibiting catabolism in rats 16 . Based on the above description, PDGF‐BB promotes proliferation 12 .…”
Section: Discussionmentioning
confidence: 97%
“…At present, the mainstream belief in the literature is that there is a correlation between the degree of cartilage damage and chondrocyte could be a potential therapeutic strategy for OA treatment A previous report showed that intra-articular injection of 10 ng/mL recombinant PDGF-BB combined with hyaluronic acid could alleviate OA by promoting the anabolism of collagen II and inhibiting catabolism in rats. 16 Based on the above description, PDGF-BB promotes proliferation. 12 We investigated whether PDGF-BB has an antiapoptotic effect in OA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, a subsequent study showed that PDGF-BB suppressed apoptosis by regulating NF-κB and PI3K/AKT pathway in IL-1β-induced human chondrocytes [10]. In 2019, an in vitro study used recombinant PDGF-BB and hyaluronic acid in combination as potent growth factors to stimulate the increased formation of chondrocytes [11]. Greene MA et al noted that targeting signaling proteins, such as JAK1/2, was a better therapeutic approach to restoring the balance in anabolic and catabolic activity in cartilage than targeting PI3K/AKT signaling [12].…”
mentioning
confidence: 99%